The Front Page Based on a Play by Ben Hecht and Charles MacArthur - Hecht, Ben; MacArthur, Charles (Criterion, 2017)
1931's "The Front Page" was added to the National Film Registry in 2010, securing its place in cinema history and its preservation for future generations to enjoy. It's easy to see why the feature was picked, presenting a sharp, incisive look at journalism of the day, finding its depiction of sensationalism and the lure of personal corruption still resonate in 2015. Bringing a popular Broadway play to the screen, director Lewis Milestone crafts a tightly wound effort that invests in speed, electing a screwball tone to balance out the grim realities in play. It's a witty picture, with finger-snap timing and shaded but bellowed performances from the cast, including Adolphe Menjou, Pat O'Brien, and Mary Brian, and one that's aware of journalism as it transforms from a pursuit of justice to demoralizing routine. While the comedy doesn't play as freshly today, intent is perfectly clear and smartly rendered. [www.blu-ray.com]
Keywords: Blu-Ray-Disc